Pengaruh Kesulitan Keuangan, CSR, dan Manajemen Laba Terhadap Penghindaran Pajak dengan Tata Kelola Perusahaan yang Baik sebagai Variabel Moderasi - Yuliansyah, Dwi Novrian; Rahayu, Sri; Yudi, Yudi (Magister Ilmu Akuntansi Universitas Jambi, 2025)
This study aims to analyze the effect of financial distress, CSR, and earnings management on tax avoidance, with GCG as a moderating variable, in palm oil companies listed on the Indonesia Stock Exchange for the period 2019–2023. Employing a quantitative method with an explanatory approach, the study observes 12 palm oil companies, yielding 60 firm-year observations. Data were analyzed using panel data regression with the CEM, based on the results of the Chow test, Hausman test, and LM test. The findings reveal that Financial distress, CSR, Earnings Management does not have a significant effect on tax avoidance. Besides, GCG positively moderates the relationship between CSR and tax avoidance, revealing a paradox in which high CSR combined with strong governance may actually encourage tax avoidance, possibly due to moral licensing based on the company's positive reputation. This study highlights that the relationship between corporate governance factors and tax avoidance is not always linear, and that the interaction effects among governance mechanisms may produce outcomes that differ from, or even contradict, theoretical expectations.